Hubungan Tingkat Stres Dengan Perubahan Tekanan Darah Pada Mahasiswa Sarjana Terapan Di Keperawatan Magelang - Karina febriana (STIKES Bethesda Yakkum, 2023)
ABSTRACT Introduction: Blood pressure can change at any time and can even change drastically. Stress is one of the triggers for changes in blood pressure. Stress can cause changes in both systolic and diastolic blood pressure. Methods: The research design is correlational analytic using a cross sectional approach. This study uses a total sampling technique of 63 respondents. The instrument in this study used the DASS 42 questionnaire with 14 stress level items for the stress level variable and a sphygmomanometer as a tool for changes in blood pressure variables. Results: The study showed that the majority of undergraduate students of applied nursing in Magelang experienced mild stress. Discussion: Mild stress is stress experienced by individuals almost every day, where stress can be counted even hours, such as sleeping a lot, having problems with classmates. Individuals who experience stress will have an impact on the vascular system, which causes events in the blood so that there is an increase in systole and diastole. The results of statistical tests stated that there was a significant relationship between stress levels and changes in systolic and diastolic blood pressure. Conclusions and suggestions: The majority of respondents experienced changes in systolic and diastolic blood pressure to get results with p values ??= 0.001 and 0.002 (p <0.05). Respondents can manage stress well and can apply healthy behavior patterns everyday.